Sequence of Numbers with Three Alternate Common Differences and Common Ratios - Rabago, Julius Fergy Tiongson (International Journal of Applied Mathematical Research, 2012)
This paper talks about two types of special sequences. The firstis the arithmetic sequence of numbers with three alternate common differences;and the other, is the geometric sequence of numbers with three alternate commondifferences. The formulas for the general term an and the sum of the firstn terms, denoted by Sn, are given respectively.